1821 Ga. Laws 593 - (:unkn) unknown (My University, 1816)
Div. 9, § 4: Prohibited challenging another, or accepting any such challenge, to duel with a sword, pistol, or other deadly weapon. Violators fined a sum of five hundred dollars and imprisoned at hard labour not less than three months nor more than one year.
Keywords: DUELING